Flypaper Effect, PAD, DAU, DAK Terhadap Belanja Daerah Di Kabupaten/Kota Di Indonesia.: Flypaper Effect, PAD, DAU, DAK on Regional Expenditures in Regencies/Cities in Indonesia. - Dewi, Santi Rahma (Universitas Muhammadiyah Sidoarjo, 2017)
This study aimed to measure how the influence of PAD, DAU, DAK to BD and whether there is a Fly Paper Effect phenomenon in each area studied. This study takes sample of the existing districts and cities in Indonesia of 112 cities and districts of 516 regency and cities in Indonesia. Secondary data is obtained by downloading the data from the Direktorat Jendral Perimbangan Keuangan Departemen Keuangan. The techniques of analysis data was used multiple linear analysis. The results of this study that PAD, DAU, DAK simultaneously affect the BD. The Fly Paper Effect phenomenon occurs in several cities and districts where the DAU coefficient value is greater than PAD, whereas DAK is only accepted by certain cities and districts that require high infrastructure development.